2021
DOI: 10.3390/met11020261
|View full text |Cite
|
Sign up to set email alerts
|

Flow Field in Slab Continuous Casting Mold with Large Width Optimized with High Temperature Quantitative Measurement and Numerical Calculation

Abstract: In this paper, the rod deflection method was applied to quantitatively measure velocity near the mold surface at high temperatures and the k-ε model coupled with a discrete phase model (DPM) was adopted to simulate the flow field in the mold. The calculated results match very well with the measured results under all the present conditions. Under the conditions of the large mold width of 1800 mm, 1.1 m/min casting speed and 140 mm submerged entry nozzle (SEN) immersion depth, the velocity near the mold surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A periodic signal r(t) with period T p can be represented in Fourier series [35], as shown in Equation (9).…”
Section: Repetitive Generalized Predict Controller (R-gpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…A periodic signal r(t) with period T p can be represented in Fourier series [35], as shown in Equation (9).…”
Section: Repetitive Generalized Predict Controller (R-gpc)mentioning
confidence: 99%
“…The level fluctuation is related to the slag entrainment [8]. As the liquid level fluctuation increases, the risk of slag entrainment also increases [9]. Thus, it is necessary a controller that can minimize the fluctuation level due to bulging and clogging disturbances and, consequently, reduce the negative effects of the mold slag entrainment.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers (Li et al , 2020; Liu and Li, 2018; Zhang et al , 2006) have recognized that metal flow in the mold is a major aspect influencing the quality of continuously cast products. The flow pattern of the mold is influenced by various process parameters such as nozzle shape, nozzle submergence depth (Ma et al , 2021), argon gas injection rate (Liu et al , 2022; Yin and Zhang, 2022) and casting speed. Additionally, it has been found that electromagnetic (EM) forces can instant alter the flow pattern, enhancing the microstructure of material and assisting in removing impurities from molten steel.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, since the width of the slab mold used for different widths of automobile exposed panels is also different, it is necessary to optimize the mold flow fields of different widths to improve the surface quality of automobile exposed panels with various widths. In view of the characteristics of the flow fields in the mold with different widths, in our recent works [18][19][20], the flow fields of slab molds with narrow, medium, and wide widths have been studied through rod deflection high-temperature measurement combined with numerical simulation. For the narrow width [18], increasing casting speed increases the subsurface velocity of molten steel and shifts down the position of the vortex core in the downward circulation zone.…”
Section: Introductionmentioning
confidence: 99%
“…For the medium width [19], when the casting speed is increased from 1.0 to 1.3, 1.5, and 2.0 m/min, the flow pattern in the mold changes from SRF to unstable flow (UF) and then to DRF. In the case of wide width [20], when the argon gas flow rate is increased from 6 L/min to 10 L/min and 14 L/min, the flow pattern changes from DRF to SRF, and the risk of slag entrainment increases. With the casting speed increased from 1.0 m/min to 1.1 m/min, the flow field pattern changes from SRF to strong DRF.…”
Section: Introductionmentioning
confidence: 99%